PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS KECERDASAN MAJEMUK UNTUK PEMBELAJARAN FISIKA SMA KELAS X PADA MATERI ELASTISITAS - Yuli Fransiska; Sardianto Markos (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2016)
Has been developed successfull the student worksheet in material elasticity of physics based multiple representation very valid and practical. The development of student worksheet is using the combination model of development and evaluation Rowntree-Tessmer. Rowntree development model consisting of three stages, namely the planning stage, the stage of development and evaluation stage. At the evaluation formative assessment presented by tessmer consisting of 5 stage, which is self evaluation , experts review, one-to-one evaluation, small group evaluation and field test. Data collection techniques using validation expert, one-to-one evaluation, small group evaluation. From the expert review obtained the percentage of the average the results of the judgment of experts byÂ  4.24 with the category of very valid. At the one-to-one evaluation obtained the results of the response of students on the use of subject matter to 83.64 percent. By the small group evaluation, the results of the response of the average student on the use of student worksheet increased from 83.64 % to 92.32 % with two categories of very good. This means that of student worksheet developed is considered to be very practical. In conclution, the results of research has got that student worksheet which is developed to be considered perfectly valid and practical, so that it can be used as student worksheet additional in a course called by in Physics in Senior High School.